Role of Objectives Alignment in Strategic Alliance Instability - Ben Jemaa-Boubaya, Kaouther; Cheriet, Foued; Smida, Ali (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2020)
The literature identifies strategic alignment as a chief determinant of the strategic alliances’ stability. Through a qualitative study based on five alliance study cases, this research aims to identify the different types of alignment and their impact on the instability. The results show that instability within an alliance can be due to the lack of alignment, i.e., of goals, agendas and structure. Differences between agendas, strategies, orientations and partners’ structures may require adjustment tools to strengthen the collaborative governance and come out of situations of instability within strategic alliances.